The Impementation of POE Learning Model (Predict Observe Explain) Assisted Magnet KIT to Improve Student Analitycal Thinking Skills - Warohomah, Fitry Mifthoh; Rahmad, M; Irawan, Dedi; Fajri, Oknain (Kasuari: Physics Education Journal (KPEJ), 2024)
This research aims to measure students' level of analytical thinking in the Natural Sciences learning process about magnetism through the POE (Predict Observe Explain) learning model with the help of a magnetic KIT (Integrated Instrument Box). The research method applied is quantitative through a Quasi Experimental design. Research instruments include interviews, questionnaires, and posttests. The research subjects were control class IX.4 which participated in the conventional learning group and experimental group IX.5 which implemented a POE model with magnetic KIT media at MTs Hasanah Pekanbaru. Data was collected through a posttest of analytical thinking skills and analyzed using descriptive analysis and the Independent Sample T test. The analysis obtained shows a significant variation in average values in the experimental and control groups, in the POE group achieving a higher level of analytical thinking (67.16%) than the conventional class (55.16%). This shows the effectiveness of POE learning with the help of magnetic KIT in improving students' analytical thinking skills regarding the context of magnetic material.